Çocuklarda Covid-19 Hastalığı: Aşı Uygulamaları ve Sağlık Çalışanlarının Rolü Geleneksel Bir Derleme - TANRIKULU, Gözdenur; KÜÇÜKOĞLU, Sibel; Taş ARSLAN, Fatma (Göbeklitepe Medical Science Journal, 2022)
Covid-19 has emerged as a serious public health emergency and has started a process that requires an urgent response. Although Covid-19 is a disease that causes higher mortality and morbidity in adults, it has been seen to affect children as well. While children play an important role in the transmission of Covid-19 infection and epidemic dynamics, they constitute a key target population for effective measures to control these outbreaks. In this direction, it was concluded that the planning and implementation of Covid-19 vaccines should include children in increasing immunity rates. Due to the fact that the Covid-19 vaccine is new and the trials on children continue, it has been observed that these conditions affect the vaccination intention of the parents. The fact that anti-vaccine and vaccine hesitancy has become an increasing problem all over the world, including in our country, has also affected the rate of Covid-19 vaccination. Healthcare workers play a key role in tackling negative attitudes towards Covid-19 vaccination. Health professionals may have responsibilities such as vaccine development, vaccine information and application, following up-to-date information about vaccine side effects, determining parents’ intentions regarding their children’s Covid-19 vaccine, and informing parents about Covid-19 vaccines. In this rewiew the Covid-19 pandemic in children, the Covid 19 vaccine applications, the role of parents and healthcare professionals have been compiled.